A Series of Advances in Analytic Interplanetary CME Modeling - C. Kay; T. Nieves‐Chinchilla; S. J. Hofmeister; E. Palmerio; V. E. Ledvina (Space Weather)
Abstract Coronal mass ejections (CMEs) and high speed streams (HSSs) are large‐scale transient structures that routinely propagate away from the Sun. Individually, they can cause space weather effects at the Earth, or elsewhere in space, but many of the largest events occur when these structures interact during their interplanetary propagation. We present the initial coupling of Open Solar Physics Rapid Ensemble Information (OSPREI), a model for CME evolution, with Mostly Empirical Operational Wind with a High Speed Stream, a time‐dependent HSS model that can serve as a background for the OSPREI CME. We present several improvements made to OSPREI in order to take advantage of the new time‐dependent, higher‐dimension background. This includes an update in the drag calculation and the ability to determine the rotation of a yaw‐like angle. We present several theoretical case studies, describing the difference in the CME behavior between a HSS background and a quiescent one. This behavior includes interplanetary CME propagation, expansion, deformation, and rotation, as well as the formation of a CME‐driven sheath. We also determine how the CME behavior changes with the HSS size and initial front distance. Generally, for a fast CME, we see that the drag is greatly reduced within the HSS, leading to faster CMEs and shorter travel times. The drag reappears stronger if the CME reaches the stream interaction region or upstream solar wind, leading to a stronger shock with more compression until the CME sufficiently decelerates. We model a CME–HSS interaction event observed by Parker Solar Probe in January 2022. The model improvements create a better match to the observed in situ profiles.